Analysis of Chinese online TV dramas based on Fiske’s TV culture theory - Zhang, Yujie (2023)
Online dramas are a new growth point for China’s TV drama industry. Moreover, the flexibility of online dramas in production and broadcasting makes them expected to become the dominant force in China’s TV drama exports.In view of the current academic research path of online dramas is unclear and the research methods lack the versatility and sustainability, this study innovatively introduces Fiske’s TV culture theory into the research of online dramas. This study applies Fiske’s TV Culture Theory and Qualitative Analysis. Fiske’s theory of television culture sees television texts as open carriers of meaning—that is, Active Texts. Viewers of TV dramas do not passively extract meaning from text, but instead actively engage in dialogue with the text as social subjects; these viewers are Active Audiences. The interpretation of any text must be linked to other texts; that is Intertextuality. This research uses triangulation to address the multiple data source issues involved in Fiske’s theory. Three Chinese TV dramas exported to Malaysia are analyzed as Activated Texts, and Fiske’s Three-level Code System is used as a structuralist framework to analyze Chinese cultural elements contained in these online drama texts. Ten Malaysian audiences of Chinese online dramas participated in this research as Active Audiences, their opinions on Chinese online dramas were obtained through semi-structured interview. In short, this study is an inheritance of Fiske’s research on television culture and a study of contemporary Chinese online dramas using structuralist narratology.